2022
DOI: 10.3390/nu14091782
|View full text |Cite
|
Sign up to set email alerts
|

Changing Dietary Habits: The Impact of Urbanization and Rising Socio-Economic Status in Families from Burkina Faso in Sub-Saharan Africa

Abstract: (1) Background: Sub-Saharan Africa is experiencing the fastest urbanization worldwide. People in rural areas still have a traditional and rural lifestyle, whereas the Westernization of diet and lifestyle is already evident in urban areas. This study describes dietary habits of families in Burkina Faso living at different levels of urbanization. (2) Methods: Data on lifestyle, socio-economic conditions, health status and anthropometry were collected from 30 families living in rural villages, a small town and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 53 publications
2
23
0
Order By: Relevance
“…Comparing our initial results to those of previous studies, it is evident that there have been changes in the prevalence and patterns of NCDs over time (53). Preliminary findings from our study identifies high rates of diabetes and hypertension among men and women in rural areas, surpassing the figures reported in previous research conducted in similar regions.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Comparing our initial results to those of previous studies, it is evident that there have been changes in the prevalence and patterns of NCDs over time (53). Preliminary findings from our study identifies high rates of diabetes and hypertension among men and women in rural areas, surpassing the figures reported in previous research conducted in similar regions.…”
Section: Discussionsupporting
confidence: 56%
“…Preliminary findings from our study identifies high rates of diabetes and hypertension among men and women in rural areas, surpassing the figures reported in previous research conducted in similar regions. This discrepancy suggests that there may have been significant shifts in the burden of these diseases within the Indian population, where traditionally the burden of these NCDs has been seen predominantly in urban cohorts (53). These findings align with previous studies that have highlighted the impact of urbanization-induced characteristics in the food and physical environments among rural areas, which promote obesity, diabetes, and other cardio-metabolic diseases (54).…”
Section: Discussionmentioning
confidence: 99%
“…The transition to a Western style of diet is now affecting a large part of the world as developing nations become more affluent and take on Western lifestyles [1][2][3]. The Western diet is characterized by higher oil, meat and sugar intakes, and by lower fiber and micronutrient intakes versus that found in most traditional diets, for example the diets that were traditionally consumed in Asia and Greece [4].…”
Section: The Western Diet and Obesitymentioning
confidence: 99%
“…There are few studies on the impact of population urbanization on human capital [74][75][76] and family capital [77,78] accumulation, but from the perspective of urbanization, it is found that the process of urbanization will affect various aspects of society [79][80][81]. In the process of population urbanization, the change in social population structure will improve the basic platform of the individual [10,62], and the individual human capital will be enhanced [75].…”
Section: Population Urbanization and Capital Compositionmentioning
confidence: 99%